Differences in food consumption of the Brazilian population by race/skin color in 2017-2018 - Janaína Calu Costa; Amanda Cristina da Silva de Jesus; Juliana Giaj Levra de Jesus; Mariana Ferreira Madruga; Thays Nascimento Souza; Maria Laura da Costa Louzada (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To evaluate food consumption in Brazil by race/skin color of the population. METHODS Food consumption data from the Pesquisa de Orçamentos Familiares (POF - Household Budget Survey) 2017-2018 were analyzed. Food and culinary preparations were grouped into 31 items, composing three main groups, defined by industrial processing characteristics: 1 - in natura/minimally processed, 2 - processed, and 3 - ultra-processed. The percentage of calories from each group was estimated by categories of race/skin color - White, Black, Mixed-race, Indigenous, and Yellow- using crude and adjusted linear regression for gender, age, schooling, income, macro-region, and area. RESULTS In the crude analyses, the consumption of in natura/minimally processed foods was lower for Yellow [66.0% (95% Confidence Interval 62.4-69.6)] and White [66.6% (95%CI 66.1-67.1)] groups than for Blacks [69.8% (95%CI 68.9-70.8)] and Mixed-race people [70.2% (95%CI 69.7-70.7)]. Yellow individuals consumed fewer processed foods, with 9.2% of energy (95%CI 7.2-11.1) whereas the other groups consumed approximately 13%. Ultra-processed foods were less consumed by Blacks [16.6% (95%CI 15.6-17.6)] and Mixed-race [16.6% (95%CI 16.2-17.1)], with the highest consumption among White [20.1% (95%CI 19.6-20.6)] and Yellow [24.5% (95%CI 20.0-29.1)] groups. The adjustment of the models reduced the magnitude of the differences between the categories of race/skin color. The difference between Black and Mixed-race individuals from the White ones decreased from 3 percentage points (pp) to 1.2 pp in the consumption of in natura/minimally processed foods and the largest differences remained in the consumption of rice and beans, with a higher percentage in the diet of Black and Mixed-race people. The contribution of processed foods remained approximately 4 pp lower for Yellow individuals. The consumption of ultra-processed products decreased by approximately 2 pp for White and Yellow groups; on the other hand, it increased by 1 pp in the consumption of Black, Mixed-race, and Indigenous peoples. CONCLUSION Differences in food consumption according to race/skin color were found and are influenced by socioeconomic and demographic conditions.